Rhabdomyomatous mesenchymal hamartoma presenting as a polypoid lesion of the nasal skin in a child: answer - Clara Gerosa; Daniela Fanni; Luca Pilloni; Filippo Carta; Roberto Puxeddu; Gavino Faa (Hygeia Press di Corridori Marinella, 2014)
Rhabdomyomatous mesenchymal hamartoma (RMH) is a rare congenital lesion of the dermis and soft tissue, first described in 1986 as a striated muscle hamartoma. It has been reported under various names: striated muscle hamartoma, congenital midline hamartoma, hamartoma of cutaneous adnexa and mesenchyme. Etiology of this lesion is unknown; it has been hypothesized that be due to an abnormal migration of mesodermal stem cells during embryiogenesis or to right genetic defects. Patients with RMH occasionally have other congenital defects. RMH usually presents as a polypoid or papular cutaneous lesion that ranges in size from a few millimeters to 1-2 cm and occurs in areas where there is a superficial striated muscle, as the nose, chin, periorbital and anterior neck areas. Here we report a case of RMH in a 2-year-old child presenting with a congenital polypoid mass on the nasal skin.